Defense and Regional Integration: Brazil’s Weapons Industry Case - Suzeley Kalil Mathias; Eduardo Lucas de Vasconcelos Cruz (Brazilian Political Science Review, 2009)
This paper works with the relation between technological development and weapons industry in Brazil, pointing out the dependence of this to that one. One reveals as the changes in the commerce of armaments that currently privileges the production of small weapons for exportation. The conclusion is that to keep projects of this nature, is using to advantage the industrial park for the dual production, that is, that one takes care the civil and the military demands. At last, it defends the possibility of the defense industry works as mechanism of regional integration.